2022
DOI: 10.1186/s12913-022-07626-x
|View full text |Cite
|
Sign up to set email alerts
|

Medical costs and hospital utilization for hemophilia A and B urban inpatients in China: a national cross-sectional study

Abstract: Background Hemophilia care in mainland China has been greatly improved since the establishment of the Hemophilia Treatment Center Collaborative Network of China (HTCCNC), and most of drugs for hemophilia have been covered by basic medical insurance schemes. This study assesses whether medical costs and hospital utilization disparities exist between hemophilia A and hemophilia B urban inpatients in China and, second, whether the prescription of coagulation factor concentrates for hemophilia A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Although the overall association between adherence and HRQoL was not significant in the multivariable analysis, the benefits of treatment adherence in improving health and psychosocial outcomes in patients with hemophilia are well documented in the literature [ 15 , 17 , 18 , 31 , 48 ]. In addition to improving functional outcomes, one Chinese study also showed that the suboptimal use of coagulation factor concentrates was associated with higher direct medical cost and healthcare use [ 49 ]. The findings collectively underscore the importance of developing strategies to improve adherence and optimize usage of prophylactic treatment in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall association between adherence and HRQoL was not significant in the multivariable analysis, the benefits of treatment adherence in improving health and psychosocial outcomes in patients with hemophilia are well documented in the literature [ 15 , 17 , 18 , 31 , 48 ]. In addition to improving functional outcomes, one Chinese study also showed that the suboptimal use of coagulation factor concentrates was associated with higher direct medical cost and healthcare use [ 49 ]. The findings collectively underscore the importance of developing strategies to improve adherence and optimize usage of prophylactic treatment in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia imposes a significant burden on affected families, 30 , 31 and the cost of genetic testing may be a barrier to implementing screening. Most interviewees indicated that the cost of screening would be a constraint affecting their decision to participate in genetic testing: “Now, the most disturbing thing is that I can’t go to work because I have to look after my son, and thus lost my source of income, having no money to support myself to participate in genetic testing.…”
Section: Resultsmentioning
confidence: 99%
“…The per patient factor cost calculated in this study was 46,990.8 CNY ($7283.7), and the median of 15,262.5 CNY ($2365.7) may be more representative due to the skewed distribution of the data. In a study of medical costs for urban hemophilia patients in China from 2010 to 2016 ( 16 ), the cost of coagulation factors for HB patients was 7,128.0 CNY ($1,104.9), and some difference between them may be due to the study being from a third-party payer perspective, including only inpatients, and having a small sample size ( n = 80). The total cost of factor IX drugs for only 341 patients amounted to 16,024,000 CNY ($2,483,763.5) a year.…”
Section: Discussionmentioning
confidence: 99%
“…However, most available studies (over 70%) on the burden of hemophilia in China did not distinguish between HA and HB or only targeted HA patients, and were conducted from a third-party perspective, analyzing direct treatment costs through health insurance system data. There is a lack of studies specifically focusing on patients with HB, where the sample size of hemophilia B patients is small or does not indicate the type of hemophilia ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%